Continuous tissue microarray based identification of cancers with homogeneous target expression for successful targeted therapy in clinical routine practice. Issue 3 (5th December 2013) - Burandt, Eike; Schreiber, Melanie; Stein, Alexander; Minner, Sarah; Clauditz, Till S.; Bokemeyer, Carsten; Jänicke, Fritz; Fisch, Margit; Izbicki, Jakob R.; Knecht, Rainald; Sauter, Guido; Stahl, Phillip R.
<x xml:space="preserve">Abstract</x> In cancer therapy, the number of drugs targeting cells with characteristic molecular aberrations is continuously rising. However, application of these new drugs still is limited to a few tumor entities. The aim of this study was to test the concept of routinely identifying all possible cancer patients who might eventually benefit from targeted therapy. Therefore, all malignant tumors routinely submitted to our Institute of Pathology over a period of 4 months were brought into a tissue microarray format. Using "in situ" methods, tumors were analyzed for HER2, EGFR, and KIT status as examples for potential therapeutic target genes. In positive cases, target heterogeneity was excluded by analyzing all available large sections. Outside of tumor entities for which targeted drugs are already approved, the study revealed six tumors with homogeneously distributed HER2 overexpression/amplification (bladder, esophageal and colorectal) and seven tumors with homogeneous EGFR amplification (vulvar, ovarian, breast, esophageal and laryngeal, and adenocarcinoma of unknown primary). A total of 151 tumors showed KIT overexpression but none of seven sequenced cases showed KIT mutations. We furthermore report on a 69‐year‐old patient with homogeneously HER2‐amplified metastatic colorectal cancer who is successfully treated by trastuzumab monotherapy. This study demonstrates that tissue microarray based screening for therapeutic target genes in tumors outside established indications represents a feasible approach suitable for routine application. The successful treatment of one patient with homogeneously HER2 positive metastatic colorectal cancer argues for the clinical utility of this approach at least in carefully selected, homogeneous cancers. © 2013 Wiley Periodicals, Inc.